2023
DOI: 10.1037/ser0000675
|View full text |Cite
|
Sign up to set email alerts
|

Changing criminal thinking: An examination of heterogeneity in treatment effects in a sample of justice-involved persons with dual diagnoses.

Abstract: Recent studies have indicated variable reductions in criminal thinking for justice-involved persons with mental illness exposed to cognitive–behavioral treatments. To date, however, no studies have identified risk factors for limited response or modeled observed disparities in responsivity to interventions aimed at reducing criminal thinking. Using an archival data set of 162 probationers with a dual diagnosis who were exposed to changing lives and changing outcomes, a latent profile analysis modeled unobserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 76 publications
1
5
0
Order By: Relevance
“…Future program evaluations should expand SUSO data collection across multiple delivery methods (e.g., group, more intensive individual, as an add-on within step-down programs), providers, and institutions. It would also be important to examine additional predictors of program completion and compliance (e.g., initial attitudes toward treatment, number of prior disciplinary infractions, history of psychosis or other indicators of psychopathology) and potential moderators (e.g., mental health symptom severity, number of prior placements in restrictive housing) that may help explain heterogeneity in treatment responsiveness such as why some individuals show reductions in PCT while others do not (Lester et al, 2022). Although self-reported measures of criminal thinking and attitudes like those used in this program evaluation are predictive of behavioral outcomes inside and outside prison walls, directly assessing these outcomes over time is also important for ensuring observed changes are not just a product of teaching people how to think differently.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Future program evaluations should expand SUSO data collection across multiple delivery methods (e.g., group, more intensive individual, as an add-on within step-down programs), providers, and institutions. It would also be important to examine additional predictors of program completion and compliance (e.g., initial attitudes toward treatment, number of prior disciplinary infractions, history of psychosis or other indicators of psychopathology) and potential moderators (e.g., mental health symptom severity, number of prior placements in restrictive housing) that may help explain heterogeneity in treatment responsiveness such as why some individuals show reductions in PCT while others do not (Lester et al, 2022). Although self-reported measures of criminal thinking and attitudes like those used in this program evaluation are predictive of behavioral outcomes inside and outside prison walls, directly assessing these outcomes over time is also important for ensuring observed changes are not just a product of teaching people how to think differently.…”
Section: Discussionmentioning
confidence: 99%
“…In one study of over 4,000 incarcerated people, behavioral and mental health variables significantly correlated with procriminal sentiments, aggression, and lowered self-control; these authors concluded that attitudinal and emotional risk factors related to reoffense are essential treatment components for those with and without serious psychological symptoms (Wolff et al, 2013). Thus, interventions for people who engage in criminal behavior and experience mental health problems, regardless of symptom severity, will be most effective when they address both concerns together (Lester et al, 2022; Morgan et al, 2012; Scanlon & Morgan, 2021)…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…At times, strategies developed to change criminal and extremist attitudes might be useful (Schumann et al, 2022). Several novel approaches incorporating cognitive behavioral and positive psychology techniques include "Taking a Chance on Change" (Folk et al, 2016), "Changing Lives and Changing Outcomes" (Lester et al, 2022), and Acceptance and Commitment Therapy-oriented interventions (Zarling and Russell, 2022). Finally, 20-30-year-old Rwandan participants in a demonstration sociotherapy project for highly traumatized youth (born to genocide perpetrators and survivors) marked by stigma, thoughts of revenge, shame, depression, and antisocial behaviors reported improved purpose in life, good relationships with others, and self-esteem, in addition to improvements in other aspects of psychological well-being (Biracyaza and Habimana, 2020).…”
Section: Implementing Purpose-inclusive Discussion In Psychiatric Man...mentioning
confidence: 99%